As leis nº 11.645/08 e 411/12 e a temática indígena nas escolas municipais de Tocantínia, estado do Tocantins - Corsino, Danilo Rodrigues (Universidade Federal do Tocantins, 2025)
This study had the general objective of understanding the effects of the implementation of laws, federal n. 11,645/2008 and municipal law no. 411/12, for municipal education in Tocantínia (TO). Municipal law no. 411/12, drawn up by two Xerente councilors and approved by the city's legislative branch, establishes the Akwẽ language as co-official at the municipal level. Federal law no. 11,645/08 decrees the mandatory teaching of indigenous histories and cultures in Brazilian schools, whether public or private. From this perspective, the present work has the specific objectives of understanding the process of including teaching the mother tongue of the Akwẽ-Xerente people, hiring Xerente professionals in the educational scenario, and continuing training for teachers. These questions were based on reference authors, documents provided by the Municipal Department of Education, municipal and federal legislation, observations of supervised curricular internship, and experiences lived as a resident among the Akwẽ people. With this, the inclusion of the Akwẽ language and the presence of professionals, both indigenous and non-indigenous, trained to teach indigenous themes in the city's educational setting, was observed.